Outsourced and invisible: Working conditions in the cleaning sector - Sardadvar, Karin (Momentum Quarterly, 2019)
This contribution investigates how cleaning work, as a typical area of low-skill work, has been subject to outsourcing in recent decades and how this outsourcing has changed that work. It presents the current characteristics and employment conditions of the Austrian cleaning sector in the international context and argues that the changes to cleaning work linked to outsourcing, especially the prevalence of working times in the early morning and late afternoon or evening, contribute to making the work invisible and, in turn, little recognized. This invisibility is also reflected in the low societal and social-scientific attention paid to low-skill service work, and cleaning in particular. The article also discusses the role of the welfare state in designing the working and living conditions of workers in low-skill services. Finally, it highlights the possibilities for improvements on different levels.